Study of the influence of tributyrin-supplemented diets on the gut bacterial communities of rainbow trout (Oncorhynchus mykiss) - A. Louvado; F. J. R. C. Coelho; M. Palma; L. J. Magnoni; F. Silva-Brito; R. O. A. Ozório; D. F. R. Cleary; I. Viegas; N. C. M. Gomes (Scientific Reports, 2024)
Abstract Dietary supplementation with triglyceride tributyrin (TBT), a butyrate precursor, has been associated with beneficial effects on fish health and improvements in the ability of carnivorous fish to tolerate higher levels of plant-based protein. In this study, we aimed to investigate the effects of a plant-based diet supplemented with TBT on the structural diversity and putative function of the digesta-associated bacterial communities of rainbow trout (Oncorhynchus mykiss). In addition to this, we also assessed the response of fish gut digestive enzyme activities and chyme metabolic profile in response to TBT supplementation. Our results indicated that TBT had no significant effects on the overall fish gut bacterial communities, digestive enzyme activities or metabolic profile when compared with non-supplemented controls. However, a more in-depth analysis into the most abundant taxa showed that diets at the highest TBT concentrations (0.2% and 0.4%) selectively inhibited members of the Enterobacterales order and reduced the relative abundance of a bacterial population related to Klebsiella pneumoniae, a potential fish pathogen. Furthermore, the predicted functional analysis of the bacterial communities indicated that increased levels of TBT were associated with depleted KEGG pathways related to pathogenesis. The specific effects of TBT on gut bacterial communities observed here are intriguing and encourage further studies to investigate the potential of this triglyceride to promote pathogen suppression in the fish gut environment, namely in the context of aquaculture.